A population‐based study of homelessness, antisocial behaviour and violence victimisation among young adults in Victoria, Australia. Issue 4 (13th April 2022) - Heerde, Jessica A.; Bailey, Jennifer A.; Patton, George C.; Toumbourou, John W.
Abstract: Homeless young adults are at increased risk for contact with the police and are overrepresented in the justice system. This study explored associations between homelessness, antisocial behaviour and violence victimisation using longitudinal panel data gathered through young adulthood. Data were drawn from a state representative population‐based sample of young adults from Victoria, Australia participating in the International Youth Development Study (IYDS; n = 2884, 54% female). Participants were surveyed at age 21 years, with follow‐up at ages 23 and 25 years. We examined changes in the prevalence of homelessness and tested hypothesised directional relationships between young adult homelessness, antisocial behaviour and violence victimisation using longitudinal cross‐lagged panel models. Multiple‐group modelling was used to test whether these relationships were moderated by gender. The prevalence of young adult homelessness was highest at age 21 (6.5%), declining at ages 23 (3.9%) and 25 years (2.5%). Results showed that young adult homelessness, antisocial behaviour and victimisation were related cross‐sectionally, but not longitudinally. Gender did not significantly moderate these associations. Findings suggest that the state of homelessness is associated with temporary vulnerability to potentially harmful and problematic situations involving antisocial behaviour and victimisation. These situations are likely to heighten risk for contact with the police and direct physical and psychological harm.